Deutsch-Englisches Code-switching zur Kontextualisierung von Emotionalitaet, Perspektivik und Bewertungen - Steiger, Kerstin (University of Waterloo, 2000)
The following thesis explores German-English code-switching as a contextualization cue in the verbal interaction. The premise is that both languages have a functional equivalence and, thus, can be used by speakers according speakers' purposes. Therefore, code-switching has an expressive quality to contextualize what is being said by how it is being said. One major argument is that this switching does not occur arbitrarily. Research has been done so far in the field to discuss grammatical constraints and sociolinguistic variables, but this thesis deals with the contextual and pragmatic strategies of changing between two different languages. Using "Gesprachsanalyse" (conversation analysis) as a method, the author shows the reciprocal use of code-switching within interactions of her own compiled corpus. She argues that code-switching follows conversational patterns and can be a marked choice of the interlocutors' language use. Three patterns are of particular interest to the analysis: the pattern of expressing feelings , perspectives, and evaluations. The corpus supports the hypothesis that code-switching is one of many contextualization cues (e.g. changing between dialect and standard) to refer to the emotionality, perspectivation, and evaluation during a conversation. After a brief introduction to the concepts and patterns of this thesis, namely emotionality, perspectivity and evaluation, a thorough analysis of code-switching in each category is presented separately in the main chapters of this thesis. However, the interdependence and coocurrence of the concepts is discussed in the fifth chapter and an interactive model is used to elaborate and illustrate the relationship among code-switching, emotion, perspectivity, and evaluation. The results show that code-switching is used to intensify, contrast and emphasize talk. Taking the context into account, it is found that code-switching has a high social relevance for communication as it creates the frame and context of interactions. This serves to support the hypothesis that the context or frame has to be negotiated during the conversation and is not prior to the social encounter.
Keywords: Harvested from Collections Canada